Postnatal expression of the lysine methyltransferase SETD1B is essential for learning and the regulation of neuron‐enriched genes. (22nd November 2021) - Michurina, Alexandra; Sakib, M Sadman; Kerimoglu, Cemil; Krüger, Dennis Manfred; Kaurani, Lalit; Islam, Md Rezaul; Joshi, Parth Devesh; Schröder, Sophie; Centeno, Tonatiuh Pena; Zhou, Jiayin; Pradhan, Ranjit; Cha, Julia; et al.
Abstract: In mammals, histone 3 lysine 4 methylation (H3K4me) is mediated by six different lysine methyltransferases. Among these enzymes, SETD1B (SET domain containing 1b) has been linked to syndromic intellectual disability in human subjects, but its role in the mammalian postnatal brain has not been studied yet. Here, we employ mice deficient for Setd1b in excitatory neurons of the postnatal forebrain, and combine neuron‐specific ChIP‐seq and RNA‐seq approaches to elucidate its role in neuronal gene expression. We observe that Setd1b controls the expression of a set of genes with a broad H3K4me3 peak at their promoters, enriched for neuron‐specific genes linked to learning and memory function. Comparative analyses in mice with conditional deletion of Kmt2a and Kmt2b histone methyltransferases show that SETD1B plays a more pronounced and potent role in regulating such genes. Moreover, postnatal loss of Setd1b leads to severe learning impairment, suggesting that SETD1B‐dependent regulation of H3K4me levels in postnatal neurons is critical for cognitive function. Synopsis: Mammalian histone H3K4 methyltransferases are linked to neurodevelopmental intellectual disability disorders. Conditional postnatal deletion studies reveal a specific role of Setd1b‐controlled gene expression programs, suggesting a potential target for treating cognitive impairment in patients. Postnatal deletion of the H3K4 methyltransferase Setd1b from neurons of the mouse forebrain leads to severe learning impairment. SETD1B in postnatal neurons controls the expression of neuron‐specific genes with a broad H3K4me3 peak, and with roles in learning and memory. Neuronal gene‐expression programs controlled by SETD1B differ substantially from those controlled by the H3K4 methyltransferases KMT2A and KMT2B. Postnatal loss of Setd1b leads to severe learning impairment in mice. Abstract : Comparative analyses of conditional deletion of mammalian H3K4 methyltransferases show a selective role for Setd1b in expression of neuron‐specific genes important for cognitive function.